YOUTH SPORTS DEVELOPMENT - Abdullaev Farhod Turdalievich (Galaxy International Interdisciplinary Research Journal, 2022)
The article analysis the importance of the sports development programs among the youth. It also gives the explanation of sports development and its benefits to the society. The social involvement in sports is described as an integral component of youth development.